Local states in an imperial world : identity, society and politics in the early modern Deccan - Fischel, Roy S. (Edinburgh University Press, 2020)
Focusing on the Deccan Sultanates of 16th- and 17th-century central India, Local States in an Imperial World promotes the idea that some polities of the time were not aspiring to be empires.